Community Response Through Social Media Accounts in Digital Communication Regional Heads in South Sulawesi - Silahuddin Genda Sila; Erniwati; Fachruddin Palapa (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study focuses on understanding how the public responds to the digital communication of regional leaders in South Sulawesi and how these interactions reflect forms of public participation in the context of digital democracy at the local level. The purpose of this study is to analyze netizens' responses to the use of Instagram social media on the accounts of four regional heads in South Sulawesi Province, namely Gowa Regent Adnan Purichta Ichsan, Makassar Mayor Ramdhan Danny Pomanto, Parepare Mayor Taufan Pawe, and North Luwu Regent Indah Putri Indriani. This study employs a qualitative method with a phenomenological approach and interactive data analysis techniques through data reduction, data presentation, and conclusion drawing supported by content analysis of comments on the Instagram accounts of the four regional heads. The results show that Instagram has become a strategic medium for building two-way communication between local governments and the community. The patterns of netizen responses varied: the accounts of the Regent of Gowa and the Regent of North Luwu were dominated by positive comments, indicating emotional closeness and public appreciation for humanistic leadership; the account of the Mayor of Makassar showed a higher intensity of criticism and public discussion, reflecting the substantive involvement of citizens in policy issues; while the Parepare Mayor's account tends to display symbolic participation with a dominance of neutral and ceremonial comments. These findings reinforce the theory of two-way symmetrical communication (Gruning & Hunt, 1984) and the concept of feedback as an indicator of successful communication (Purba et al., 2020), while also showing that social media can function as an instrument of public accountability and digital democracy. However, this study also found a gap between high digital access and the quality of community participation. The majority of public interactions are still emotional and symbolic, while substantive criticism of policies is not yet widespread. Therefore, the effectiveness of social media as a space for public deliberation greatly depends on the extent to which regional heads are able to manage community feedback responsively and use it as a basis for policy formulation. This study emphasizes the need for a more participatory, transparent, and good governance-oriented digital communication strategy so that social media can truly function as a bridge of democracy between local governments and the community.